Chapter 7 Hva sier de til seg selv? - Reinboth, Michael S. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The purpose of this study was to examine the self-talk of elite triathletes during a competition. Furthermore, we wanted to investigate possible differences in content and frequency in self-talk during a triathlon competition among elite and club triathletes. Participants were ten members of the Norwegian triathlon national team as well as ten triathletes competing at Norwegian club level. The competition consisted of an indoor sprint-distance triathlon (a 750 m pool swim leg, a 20 km ergometer cycling leg, and a 5 km treadmill run leg). Self-talk content and frequency were measured using a Norwegian version of the Automatic Self-Talk Questionnaire for Sports (ASTQS). Overall, results showed that all athletes reported more positive than negative self-talk during competition. Moreover, elite athletes reported more confidence-inducing self-talk compared to the club level athletes during the swim. The findings also indicated that elite athletes were more able than club athletes to maintain higher levels of positive self-talk during the latter stages of the competition (5 km run). This tendency was reversed regarding negative self-talk. Elite athletes reported less negative self-talk compared to club level athletes towards the end of the competition."